METODE BIOSTIMULASI KOMPOS KACANG TANAH UNTUK BIOREMIDIASI TANAH TERCEMAR MINYAK BUMI - Prasetyo Handrianto, ; Yuni Sri Rahayu, ; Yuliani, (Matematika dan Sains, 2011)
The aims of research are to find the effect of the peanut compost in decreasing TPH value of soil polluted petroleum and to know the optimal compost concentration to increase the N concentration. This research used the group randomized design with one treatment, namely concentration of peanut compost. Results of research showed that concentration of N, P, K elements in peanut compost were 1.15 %, 0.10 % and 0.73 %, respectively. The peanut compost with concentration of 385 g/kg soil, 500 g/kg soil, and 636 g/kg soil gave effect to decrease TPH value and to increase the N elements in soil polluted petroleum.